A Constructionist Review of Morality and Emotions: No Evidence for Specific Links Between Moral Content and Discrete Emotions. (November 2015) - Cameron, C. Daryl; Lindquist, Kristen A.; Gray, Kurt
Morality and emotions are linked, but what is the nature of their correspondence? Many "whole number" accounts posit specific correspondences between moral content and discrete emotions, such that harm is linked to anger, and purity is linked to disgust. A review of the literature provides little support for these specific morality–emotion links. Moreover, any apparent specificity may arise from global features shared between morality and emotion, such as affect and conceptual content. These findings are consistent with a constructionist perspective of the mind, which argues against a whole number of discrete and domain-specific mental mechanisms underlying morality and emotion. Instead, constructionism emphasizes the flexible combination of basic and domain-general ingredients such as core affect and conceptualization in creating the experience of moral judgments and discrete emotions. The implications of constructionism in moral psychology are discussed, and we propose an experimental framework for rigorously testing morality–emotion links.